2014
DOI: 10.1016/j.biopsycho.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Frontal alpha EEG asymmetry before and after behavioral activation treatment for depression

Abstract: Background Mid-frontal and mid-lateral (F3/F4 and F7/F8) EEG asymmetry has been associated with motivation and affect. We examined alpha EEG asymmetry in depressed and healthy participants before and after Behavioral Activation treatment for depression; examined the association between alpha EEG asymmetry and motivational systems and affect; and evaluated the utility of alpha EEG asymmetry in predicting remission. Methods Depressed (n = 37) and healthy participants (n = 35) were assessed before and after tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 71 publications
6
87
0
Order By: Relevance
“…In contrast, EEG activation of the right-side frontal cortex was related to withdrawal of related emotions and the pathophysiology of depression [44]. In a recent study, alpha EEG asymmetry was found to be significantly higher in MDD patients compared to healthy controls [46]. A number of studies reported a decrease in the right frontal area relative to the left side [47][48][49][50].…”
Section: Eeg Alpha Asymmetrymentioning
confidence: 93%
“…In contrast, EEG activation of the right-side frontal cortex was related to withdrawal of related emotions and the pathophysiology of depression [44]. In a recent study, alpha EEG asymmetry was found to be significantly higher in MDD patients compared to healthy controls [46]. A number of studies reported a decrease in the right frontal area relative to the left side [47][48][49][50].…”
Section: Eeg Alpha Asymmetrymentioning
confidence: 93%
“…In their review of the role of frontal EEG asymmetry, Coan and Allen [38] noted that, although there was some evidence that Ra>La cerebral activation was associated with depression and that stability of that asymmetry was demonstrated in clinically depressed patients over 16 weeks [50], prospective or intervention studies were required to conclusively estimate the strength of that relationship. One such recent intervention study was reported by Gollan et al [51] and described several important aspects of the association in question. First, Gollan et al [51] showed that the depressed participants in their study had significantly greater frontal asymmetry than healthy participants prior to the delivery of behavioural activation therapy to the former.…”
Section: Frontal Lobe Asymmetry and Depressionmentioning
confidence: 94%
“…One such recent intervention study was reported by Gollan et al [51] and described several important aspects of the association in question. First, Gollan et al [51] showed that the depressed participants in their study had significantly greater frontal asymmetry than healthy participants prior to the delivery of behavioural activation therapy to the former. Second, there were significant correlations between frontal asymmetry and negative affect and behavioural inhibition measured via questionnaire.…”
Section: Frontal Lobe Asymmetry and Depressionmentioning
confidence: 94%
See 2 more Smart Citations